TRANSGENIC TOBACCO PLANTS EXPRESSING GENE EcCspA TEND TO BE COLD RESISTANT - Nizkorodova, A.S.; Iskakov , B.K. (Eurasian Journal of Applied Biotechnology, 2014)
One of the most promising directions in creation of transgenic cold resistant plants is constitutive expression of transgenic RNA-chaperons. RNA-chaperons are proteins that bind nucleic acids (single stranded RNA and DNA) and destabilize their secondary structures which are formed by the decrease of temperature. Cold-shock proteins (CSP) are RNA-chaperons which present in all living organisms. The main cold-shock protein of E. coli CSPA is consist of 70 amino acids and binds single stranded RNAs and DNAs nonspecifically. We have obtained several lines of transgenic tobacco Nicotiana tabacum var. Samsun constitutively expressing protein EcCSPA in cytoplasm. There were nine transgenic tobacco lines carrying transgen EcCspA (marked as “A” with number) and three transgenic lines carrying transgen EcCspA which had 5’-untranslated region (UTR) of potato virus Y upstream (marked as “YA” with number). 5’-UTR of potato virus Y is well known translational enhancer; we used it for expression enhancement of goal protein in transgenic plants. We explored tolerance of transgenic plants to chilling and freezing. Three transgenic lines demonstrated 100% survival under the conditions of cold shock (lines A-20, YA-17 and YA-20). Two of transgenic lines namely YA-20 and A-27 showed statistically valid increase in raw weight of plants green part after the cold shock. The raw weight gain was 30% (YA-20) and 57% (A-27) in compare with control plants. Thus, we constant economical expediency of creation of cold-resistant agricultural plants transgenic by EcCspA.